2022
DOI: 10.1021/acs.iecr.2c01222
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of CoS Nanoparticles Anchored on the Surface of Functionalized Multiwalled Carbon Nanotubes as Cathode Materials for Advanced Li–S Batteries

Abstract: The effects of CoS loading (10, 20, and 30%) on multiwalled carbon nanotubes (MWCNTs) on electrochemical performance for Li−S batteries were investigated. A facile hydrothermal method was used to grow CoS nanoparticles in situ on the surface of MWCNTs. In addition, CoS on functionalized multiwalled carbon nanotubes (f-MWCNTs) was also investigated. Scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and Xray photoelectron spectroscopy were used to characterize the structure and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…48 The peaks at 285.6 and 286.8 eV were assigned to C−O−Sb and C−S bonding, further demonstrating the successful formation of interfacial bonding between MWCNTs and Sb 2 S 3 . 28,48 The existence of C−S/C−O−Sb bonds also suggests that the defective MWCNTs could effectively anchor Sb 2 S 3 and confine the sodiated sulfides from aggregation. Undoubtedly, the interfacial chemical linkage is profitable for suppressing the interfacial charge transfer impendence and maintaining the structural integrality of the MWCNTs/Sb 2 S 3 -M electrode during repeated charge/discharge processes.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…48 The peaks at 285.6 and 286.8 eV were assigned to C−O−Sb and C−S bonding, further demonstrating the successful formation of interfacial bonding between MWCNTs and Sb 2 S 3 . 28,48 The existence of C−S/C−O−Sb bonds also suggests that the defective MWCNTs could effectively anchor Sb 2 S 3 and confine the sodiated sulfides from aggregation. Undoubtedly, the interfacial chemical linkage is profitable for suppressing the interfacial charge transfer impendence and maintaining the structural integrality of the MWCNTs/Sb 2 S 3 -M electrode during repeated charge/discharge processes.…”
Section: Resultsmentioning
confidence: 88%
“…Another pair of peaks at 162.9 and 161.8 eV were regarded as the Sb–S bond of S 2p 1/2 and S 2p 3/2 . Two peaks at 169.0 and 170.1 eV should be connected with some oxysulfide species. , As for high-resolution C 1s spectrum (Figure d), the position located at 284.8 eV corresponded to the C–C/CC bond of MWCNTs . The peaks at 285.6 and 286.8 eV were assigned to C–O–Sb and C–S bonding, further demonstrating the successful formation of interfacial bonding between MWCNTs and Sb 2 S 3 . , The existence of C–S/C–O–Sb bonds also suggests that the defective MWCNTs could effectively anchor Sb 2 S 3 and confine the sodiated sulfides from aggregation.…”
Section: Resultsmentioning
confidence: 97%
“…The reaction is responsible for the production of subspecies of polysulfides which are highly soluble in organic electrolytes typical of Li-S batteries. Several methods have been proposed to curb the transfer of resistive sulfide species to the anode or their dissolution into the electrolyte: engineering of the carbon surface with functional groups to chemically anchor the polysulfides to the carbon pores [1]; employing catalytic transition metal nitrides, sulfide, or oxides to increase the efficiency of the chain reaction [2,3]; or physical entrapment of sulfur into conductive matrices [4,5] to limit the deposition of resistive lithium sulfides at the anode. Previous efforts have shown that capacity degradation of the lithium-sulfur system stems from the higher discharge plateau [6], since that is where nonrecoverable products of the redox reaction involving long Energies 2024, 17, 2168 2 of 10 chain polysulfide are formed; therefore, efforts to create carbon-sulfur nanocomposites and the confinement of sulfur would cull the full reduction in polysulfide chain products, as wrapped sulfur sites would act as sites with limited lithium reactivity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted much attention as potential supercapacitor electrode materials. [7][8][9][10][11][12][13] In particular, cobalt sulfides with high electrical conductivity have been widely studied in many applications due to their excellent electrochemical properties 14 Much work has gone into creating different cobalt sulfide nanostructures over the last 20 years, including nanoparticles 15,16 nanosphere, 17 nanorods, 18,19 nanoarrays, 20 nanoneedles, 21 nanosheets, 22 nanofilms, 23 and hollow nanostructures, [24][25][26][27] for use in electrochemical energy storage systems. Among these structures, hollow nanostructures are expected to deliver superior performance because of the following advantages.…”
Section: Introductionmentioning
confidence: 99%